KETIMPANGAN PERAN DAERAH DALAM IMPLEMENTASI KEBIJAKAN DTKS: PENGALAMAN KABUPATEN LIMA PULUH KOTA - Dela Kurnia; Rahmadani Yusran (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to analyze the implementation of the Integrated Social Welfare Data (DTKS) policy at the Social Affairs Office of Lima Puluh Kota Regency, focusing on the distribution of authority between central and local governments. Using a descriptive qualitative approach, data were collected through in-depth interviews and documentation, and analyzed thematically within the framework of Van Meter and Van Horn’s policy implementation theory. The findings indicate a significant imbalance in roles, with central government dominance over data proposal, verification, and finalization processes. Weak vertical coordination, limited local authority, and the closed nature of the central system hinder the responsiveness of DTKS to local social conditions. The study concludes that successful DTKS implementation requires redistributing authority, improving intergovernmental communication, and strengthening local institutional capacity to ensure more adaptive and participatory policy outcomes.